Effect of soils, cropping system and host phenotype on incidence and severity of Striga gesnerioides on cowpea in West Africa - Cardwell, K.F.; Lane, J.A. (Elsevier, 1995)
Striga gesnerioides, a plant parasitic phanerogam, is a known constraint to cowpea production in the sahelian and northern guinea savanna zones of West and Central Africa. A survey was done in 1990 across six countries to collect data on soil types, cowpea phenotype, and cropping systems with relation to incidence and severity of striga on cowpea. Of the 153 fields visited, 40% were infested with S. gesnerioides. Generally, the severity of the parasitic weed was light, with a mean rating of 1.5 on a scale of 1 to 5. A high correlation was found between incidence of striga and the amount of sand in the soil. Of the 153 sites only 27 had no sand in the soil. Of those 27, only three (11%) had some S. gesnerioides compared with 50% on sandy soils. A database was compiled on cowpea phenotypes and the cropping systems in which they are used. Severity of striga infestation per cowpea plant decreased somewhat from east to west, though it is unclear whether this was a function of cowpea genotype or striga pathotype. The predominant cropping systems where striga infestation occurred were sole cowpea, intercrop with millet, and with sorghum. Fields in rotation with cotton, or intercropped with vegetables and legumes were always striga-free.